Аналіз напружено-деформованого стану опорно-поворотного пристрою автокранів з урахуванням жорсткості опор - Федик, В. В.; Малащенко, В. О.; Ланець, О. В. (НТУ "ХПІ", 2015)
У статті розглянуто напружено-деформований стан основних деталей опорно-поворотного пристрою автомобільних кранів з урахуванням жорсткісних характеристик зубчастого вінця та півобойм за методом скінчених елементів. Встановлено закономірності розподілення контактних напружень на торцях роликів та за їх довжиною. Виявлено наявність двох зон з максимальними контактними напруженнями та зменшення його величини на основній контактній лінії. Встановлено, що нерівномірність навантаження ролика відповідає умовам рівноваги, оскільки рівнодіюча сила від дії тиску на обох його сторонах буде однакова, але в результаті обертання ролика навколо своєї осі пікові навантаження дещо збільшуються по відношенню до таких, які виникають на іншій його стороні.

In the article the stress-strain state of the main parts of the supporting rotary crane trucks considering stiffness characteristics of ring gear by finite element method. Analysis of stress-strain state for rollers taking into account of real parameters for basic elements executed, such as rigidity of the Rings and geometry of location rollers on treadmills. The regularities of distribution of contact stresses at the ends of rollers and their length. Revealed the presence of two zones of maximum contact stresses and reduce its size in the main contact line. Established that the uneven load roller meets the conditions of equilibrium because of the resultant force of pressure on both of its sides is the same, but the rotation of the roller about its axis peak slightly increased relative to those arising in another of his side. The obtained results in the paper can be the main base for further research supporting-turning devices crane trucks, excavators and other handling machines.
The analysis of stress-strain state of automobile crane supporting-turning device with taking into account inflexibility of supports
Keywords: контактне напруження; зубчастий вінець; метод скінченних елементів; навантаження; ролик; рівновага; cranes; supporting-turning device; contact stress